(3OQGSI JMdjdjI JCUjdjI ebGQfI aj GdJTQjYGJ GdGQOfjI h GdShQjI h GddHfGfjI h GdeUQjI h GdaQfSjI h ZjQgGs - (3GfhQ eMeO UObj(B, (3GdeSGYOIs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2009)
(3eGgjI GdLQjeI GdGbJUGOjI h GdYfGUQ GdeDKQI HgG , GdefGgL GdJTQjYjI aj ehGLgJgG , WHjYI GdfehPL GdbGfhfj ddQcf GdeGOj aj GdLQGFe GdGbJUGOjI , ehVY GdTQhY h GdGTJQGc GdLQej aj GdLQGFe GdGbJUGOjI , fWGb GdWHjYI GdbGfhfjI GdNGUI ddLQGFe GdGbJUGOjI aj UhQJj GdbUO h GdNWC eOi GaJQGV GdYde h GdGQGOI aj GdLQGFe GdGbJUGOjI , eOi EbUGA GdQcf GdeYfhj aj GdLQGFe GdGbJUGOjI dUGdM GdQcf GdeGOj , GdGNJUGU GdGSJKfGFj ddfjGHI GdYGeI aj GdLQGFe GdGbJUGOjI , fXGe GdeUGdMI aj GdLQGFe GdGbJUGOjI , GdGNJUGU GdbVGFj aj GdLQGFe GdGbJUGOjI , GSfGO GdeSDhdjI GdLRGFjI Gdi GdZjQ aj GdLQGFe GdGbJUGOjI , GSfGO GdeSDhdjI GdLRGFjI Gdi GdTNU GdeYfhj aj GdLQGFe GdGbJUGOjI(B.s
(3eQGLY U(B.437s
Keywords: (3GdLQGFe GdGbJUGOjIs; (3GdbGfhf GdLfGFjs; (3GdeSDhdjI GdLRGFjIs